Inhibition of Mitochondrial Division Attenuates Cisplatin-Induced Toxicity in the Neuromast Hair Cells - Vargo, Jonathon W.; Walker, Steven N.; Gopal, Suhasini R.; Deshmukh, Aditi R.; McDermott Jr., Brian M.; Alagramam, Kumar N.; Stepanyan, Ruben (Frontiers in Cellular Neuroscience, 2017)
Cisplatin and other related platinum antineoplastic drugs are commonly used in the treatment of a variety of cancers in both adults and children, but are often associated with severe side effects, including hearing loss. Cisplatin’s ototoxic effects are multifaceted, culminating in irreversible damage to the mechanosensory hair cells in the inner ear. Platinum drugs act on cancerous cells by forming nuclear DNA adducts, which may initiate signaling leading to cell cycle arrest or apoptosis. Moreover, it was reported that cisplatin may induce mitochondrial DNA damage in non-cancerous cells. Therefore, protecting mitochondria may alleviate cisplatin-induced insult to non-proliferating cells. Although, it is important to identify agents that shield the mitochondria from cisplatin-induced insult without compromising the anti-tumor actions of the platinum-based drugs. In this study we tested the protective properties of mitochondrial division inhibitor, mdivi-1, a derivative of quinazolinone and a regulator of apoptosis and mitochondrial fission and fusion. Interestingly, it has been reported that mdivi-1 increases the apoptosis of cells that are resistant to cisplatin in both in vitro and in vivo studies. The ability of mdivi-1 to protect hair cells against cisplatin-induced toxicity was evaluated in a fish model. Wild-type (Tübingen strain), cdh23 mutant, and transgenic pvalb3b::GFP zebrafish stably expressing GFP in the hair cells were used in this study. Larvae at 5 – 6 days post fertilization were placed in varying concentrations of cisplatin (50 – 200 μM) and/or mdivi-1 (3 – 10 μM) for 16 hours. To evaluate hair cell’s viability the number of hair bundles per neuromast were counted. To assess hair cell function, we used the FM1-43 uptake assay and recordings of neuromast microphonic potentials. Results showed that mdivi-1 protected hair cells of lateral line neuromasts when they were challenged by 50 μM of cisplatin: viability of hair cells increased almost twice from 19±1.8% to 36±2.0% (p < 0.001). No protection was observed when higher concentrations of cisplatin were used. Our data were in accord with previously reported results that functional mechanotransduction strongly potentiates cisplatin-induced hair cell toxicity. Together, our data suggests that mitochondrial protection may prevent cisplatin-induced damage to hair cells.